ByzRev 06.2024.015: Cilliers Breytenbach – Elli Tzavella, Early Christianity in Athens, Attica, and Adjacent Areas.: From Paul to Justinian I (1st–6th cent. AD) (Early Christianity in Greece 1 = Ancient Judiasm and Early Christianity 114). Leiden – Boston: Brill 2023. - Schäfer, Felix (The Byzantine Review, 2024)
Cilliers Breytenbach – Elli Tzavella, Early Christianity in Athens, Attica, and Adjacent Areas. From Paul to Justinian I (1st–6th cent. AD) (Early Christianity in Greece 1 = Ancient Judiasm and Early Christianity 114). Leiden – Boston: Brill 2023. XXVI, 599 S. – ISBN 978-90-04-50960-3 (€ 174,41)